1996
DOI: 10.1002/(sici)1096-8628(19960216)67:1<103::aid-ajmg18>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between a DNA sequence variant in the serotonin 2A receptor gene and schizophrenia

Abstract: Sixty‐two patients with schizophrenia and 96 normal controls were investigated for genetic association with restriction fragment length polymorphisms (RFLPs) in the serotonin receptor genes. A positive association between the serotonin 2A receptor gene (HTR2A) and schizophrenia was found, but not between schizophrenia and the serotonin 1A receptor gene. The positive association we report here would suggest that the DNA region with susceptibility to schizophrenia lies in the HTR2A on the long arm of chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
3
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 13 publications
1
52
3
1
Order By: Relevance
“…For example, DRD2 À141delC 3 and Taq I A 4 polymorphism caused a functional change of the product, and both are reported to have an association with antipsychotic response. 5,6 HTR2A 102T4C polymorphism showed an association with the presence of schizophrenia, 7 and À1438G4A polymorphism with a clozapine response. 8 In addition, HTR2A H452Y polymorphism, which caused a functional change of the expressed gene product, 9 is reported to be involved in clozapine response.…”
Section: Introductionsupporting
confidence: 87%
“…For example, DRD2 À141delC 3 and Taq I A 4 polymorphism caused a functional change of the product, and both are reported to have an association with antipsychotic response. 5,6 HTR2A 102T4C polymorphism showed an association with the presence of schizophrenia, 7 and À1438G4A polymorphism with a clozapine response. 8 In addition, HTR2A H452Y polymorphism, which caused a functional change of the expressed gene product, 9 is reported to be involved in clozapine response.…”
Section: Introductionsupporting
confidence: 87%
“…In addition, there was no clear trend of differential distribution between patients and controls. These results could not confirm previous findings of association with schizophrenia [Inayama et al, 1996;Williams et al, 1996;Joober et al, 1999;Araga and Narasu, 2002]. However, it is likely that serotonergic associations are stronger when specific phenotypes such as suicidal behaviour and clinical dimensions are considered [Bonnier et al, 2002;Golimbet et al, 2002] and therefore could not be detected in our sample.…”
Section: Discussioncontrasting
confidence: 88%
“…However, association and linkage genetic studies have failed to produce consistent results supporting the involvement of serotonergic mutations in mental illnesses such as schizophrenia and bipolar disorder. Polymorphisms in the gene coding for 5-HT2A receptors have been related to schizophrenia, bipolar disorder and psychotic symptomatology [Inayama et al, 1996;Williams et al, 1996;Du et al, 1999;Joober et al, 1999;Nacmias et al, 2001;Araga and Narasu, 2002;Bonnier et al, 2002;Golimbet et al, 2002]. Genetic variants of the serotonin transporter (5-HTT) have also been associated with psychotic disorders Malhotra et al, 1998;Hranilovic et al, 2000;Kaiser et al, 2001;Tsai et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…These workers suggested that this gene, or a locus in linkage disequilibrium with it, conferred susceptibility to schizophrenia because the proportion of allele 2 and genotype 2/2 of the T102C polymorphism was higher than expected in schizophrenic patients and was associated with the pathogenesis of this condition. Although similar results were observed in Japanese patients and controls (Inayama et al, 1996), the findings of Williams et al have been criticized by various authors (Clifford and Nunez, 1996;Malhotra et al, 1996;Arranz et al, 1996;Sasaki et al, 1996;Crow, 1996). The investigations of Williams et al and Inayama et al were repeated in another study by Erdmann et al (1996) who demonstrated that there was structural variability (2 amino-acid substitutions) in the human 5-HT 2a receptor but that receptor variants were encountered at similar frequencies in both schizophrenic individuals and normal controls, indicating that the presence of these variants were not etiologically related to schizophrenia.…”
Section: Reviewmentioning
confidence: 99%